NEXT GENERATION NEUROLOGY. Issue 12 (15th November 2016) - Marchment, Deepti; Rohrer, Jon; ,; Devine, Helen
Abstract : Background: To ensure that neurology continues to recruit the brightest and best trainees we aim to understand the factors that influence junior doctors to make this specialty choice. Methods: We analysed the application forms of all junior doctors wishing to become mentees in the ABNT Mentoring Programme over the last two years to evaluate why they were interested in neurology and any limitations they had experienced in exploring this career choice. Results: Forty-one trainees applied (59% female, 90% Foundation-level doctors). 48% of respondents were 90–100% sure that they wanted to specialise in neurology. All respondents were over 60% sure of their choice. The most common attraction to neurology cited was academic interest (80%), followed by: intellectual challenge (66%); previous clinical experiences (51%); patient population (39%); and emphasis on clinical diagnostic skills (34%). Challenges junior doctors experienced included: gaining clinical exposure to neurology (61%); gaining related research and audit experience (46%); competition to secure a training number (37%); lack of career advice (20%); and achieving a work/life balance (15%). Conclusions: By increasing the exposure to neurology through provision of clinical tasters, research and audit opportunities, and career advice, we can continue to competitively attract high-calibre juniors to become neurology trainees.